First‐In‐Human Study of Safety, Tolerability, Efficacy, and Pharmacokinetics of CPNE7‐Derived Peptide (Selcopintide) for Dentin Hypersensitivity - Myung Jin Lee; Yoon Seon Lee; Joo‐Cheol Park; Hyun Chul Kim; So Hyun Park; Howard Lee; Won Jun Shon (Clinical and Translational Science)
ABSTRACT Dentin hypersensitivity is characterized by transient, sharp pain resulting from dentin exposure due to enamel or cementum loss. Current treatments, which primarily focus on superficial tubule occlusion or nerve desensitization, provide only temporary relief. Copine7 (CPNE7) induces odontoblast differentiation and physiologic dentin regeneration, enabling biological dentin sealing and presenting a novel therapeutic approach. This study reports the first‐in‐human results of a randomized, double‐blind, dose‐escalation phase 1/2a clinical trial evaluating the safety, tolerability, preliminary efficacy, and pharmacokinetics of the CPNE7‐derived functional peptide (selcopintide) in patients with dentin hypersensitivity. In Part A (Single Ascending Dose, SAD), 24 participants received a single topical application of selcopintide at ascending doses (2.5, 5, and 10 μg/tooth) in a 6:2 randomization ratio (treatment: placebo). In Part B (Multiple Ascending Dose, MAD), 16 participants received three topical applications (5 and 10 μg/tooth) over 15 days (day 1, 8, and 15; visits 2–4) with the same randomization ratio. Efficacy endpoints were assessed by changes in cold water, evaporative air, and tactile sensitivity. In Part B, the 10 μg selcopintide group demonstrated statistically significant reductions from the baseline across all three measures (p < 0.05), with a mean decrease of −23.2 ± 19.4 mm in VAS, the primary efficacy endpoint. All doses were well tolerated, with no serious adverse events and no detectable systemic absorption of selcopintide. These findings support the safety, tolerability, and preliminary efficacy of selcopintide as a novel therapeutic candidate for the treatment of dentin hypersensitivity.